PHARMACOLOGICALLY TARGETING AGING SLOWS AGE-RELATED BONE LOSS - Melov, S. (Innov Aging, 2017)
There is considerable interest in determining whether chemical compounds or interventions shown to significantly increase longevity in invertebrate models will also affect aging in mammals. To explore this concept, we tested three compounds and one element for their ability to slow age-related bone micro-architecture and functional decline in older mice. We chronically treated mice from 19 months of age and used a repeated measures experimental design to evaluate a number of structural and functional indices over late life. We focused on the aging skeleton, particularly the femur, because it can be accurately observed by computed tomography (CT) in living animals. Findings in this tissue may provide important insights into a major health issue, age-related bone loss and fracture in humans. We observed that with age there was increased inter-animal variation in bone structure despite the genetically identical nature of the test population. We also discovered complex changes in femoral bone loss and architecture during late life; the latter, osteopenic changes being similar to those observed in humans. In addition, we were able to document that the incidence of spontaneous fractures in aged mice is similar to that for humans. Finally, we report that one of the four interventions tested reduced the rate of bone loss in mice to a level similar to that seen with anti-osteoporotic drugs in humans. Our results demonstrate that selecting interventions on the basis of lifespan extension in invertebrates may be predictive of positive healthspan effects in aging mammals.